Performance of Broilers Fed Diets Supplemented with a Phytogenic Mixture as an Alternative of Antibiotic Growth Promoters - Singh, Vikash Vikram; Singh, Vijay Kumar; Tewari, Dharmesh; Gautam, Sachin; Singh, Virendra Bahadur; Singh, Prateek (Indian Journal of Animal Nutrition, 2019)
In order to evaluate the effect of a phytogenic mixture on the performance of broiler chickens two hundred fifty Vencobb-400Y strain day old broiler chicks were randomly divided into five groups randomly and kept either on basal diet without any supplement (NCON), basal diet + antibiotic (PCON), basal diet + 1% phytogenic mixture (LPH), basal diet + 2% phytogenic mixture (MPH) and basal diet + 3% phytogenic mixture (HPH) for 35 days. The phytogenic mixture supplemented group’s birds had higher body weight than the control group birds and the mean body weight of LPH, MPH and HPH was significantly (P